2020
DOI: 10.1590/1516-4446-2018-0272
|View full text |Cite
|
Sign up to set email alerts
|

The first instrument for complex PTSD assessment: psychometric properties of the ICD-11 Trauma Questionnaire

Abstract: Objective: The ICD-11 Trauma Questionnaire (ITQ) was developed as a joint effort by researchers from several countries to evaluate post-traumatic stress (PTSD) and complex-PTSD (C-PTSD) symptoms. This study is part of a multi-center international collaborative research project that aims to provide psychometric support for this initial instrument in different languages, considering the specific contexts related to complex traumatization. This study verified the psychometric characteristics of the Portuguese ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…According to ICD-11 diagnostic guidelines, a person may receive a possible diagnosis for PTSD or cPTSD, but not both. For both scales, reliability was good with α = 0.84 for the PTSD scale and α = 0.88 for the cPTSD scale ( 53 ). The German version has been validated in a representative population-based sample and can be used for research and clinical practice ( 54 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to ICD-11 diagnostic guidelines, a person may receive a possible diagnosis for PTSD or cPTSD, but not both. For both scales, reliability was good with α = 0.84 for the PTSD scale and α = 0.88 for the cPTSD scale ( 53 ). The German version has been validated in a representative population-based sample and can be used for research and clinical practice ( 54 ).…”
Section: Methodsmentioning
confidence: 99%
“…Karatzias et al ( 2016 ) found weak factor loadings (< .60) for seven out of nine items on the affect dysregulation scale. Hyland et al ( 2017 ) report higher factor loadings, > .70 for six out of nine items, whereas Rocha et al ( 2019 ) propose that affect dysregulation should be split into three different factors. The samples in the above studies vary in the extent and type of traumatic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of this research has been restricted to high-income countries (HICs), whereas significantly fewer studies have analysed samples from low- and middle-income countries (LMICs); e.g. Uganda (Dokkedahl, Ovuga, & Elklit, 2015 ; Murphy, Elklit, Dokkedahl, & Shevlin, 2016 , 2018 ); Angola (Rocha et al, 2019 ); Ghana, Kenya, and Nigeria (Ben-Ezra et al, 2020 ; Owczarek et al, 2020 ); Ukraine (McElroy et al, 2019 ; Shevlin et al, 2018 ); and Lebanon (Hyland et al, 2018 ; Vallières et al, 2018 ). Further research in LMICs is therefore necessary to determine whether ICD-11 criteria for PTSD and CPTSD are internationally relevant.…”
Section: Introductionmentioning
confidence: 99%